THE CENTRAL BANK’S POLICY JUSTIFICATION IN MITIGATING CLIMATE CHANGE - Muchammad Chanif Chamdani; Bramanda Sajiwo Santoso (Bank Indonesia, 2023)
In recent years, increasing awareness of the impact of climate change has attracted the attention of central banks in a number of countries. Under their authority, some central banks have started to formulate “green policies.” These green policies include a green version of quantitative easing, buying green bonds in order to support the growth of environmentally friendly financial institutions, and imposing restrictions or prohibitions on non-environmentally friendly industry lending by banks. Bank Indonesia itself is starting to explore banking policies that are more environmentally friendly, one of which is by managing financial instruments in a sustainable manner and providing green incentives. This raises unavoidable questions about the legitimacy of Bank Indonesia’s promulgation of these environmentally friendly bankingpolicies and the issues of independence, accountability and legitimacy that accompany them. This research found that green finance policies were adopted by Bank Indonesia due to its flexibility and/or independence in deploying various policy instruments, the expansion of Bank Indonesia’s mandate to maintain financial system stability, institutional relationships, and involvement in various green financial forums. However, further discussion shows that this expansion of its mandate simultaneously affects the independence of the central bank leading to issues surrounding the accountability and even legitimacy of the central bank